Construction of cyberspace security course system of comprehensive practice and graded customs clearance - Kai CHEN; Cai FU; Deqing ZOU; Weizhong QIANG; Yongquan CUI; Lansheng HAN (网络与信息安全学报)
The demand of cyberspace security promotes the development of cyberspace security,and the core task of the development of cyberspace security is to train high-quality professionals.In view of the problems existing in the current training of cyberspace security talents,such as scattered knowledge system,lagged professional knowledge,independent course content and insufficient interest in learning,according to the students' learning rules and cognitive process,a top-down approach is adopted to construct the curriculum system,aggregate and refine practical knowledge and skills,and a hierarchical training model of cyberspace security comprehensive practice is put forward.Breaking through the traditional learning assessment mechanism,the customs clearance mode of game is introduced.By setting test barriers for each knowledge and skill point,each training level and final comprehensive training students' ability level is examined in the way of actual customs clearance finally.Therefore,the course system of comprehensive practice and graded customs clearance of cyberspace security is constructed in order to cultivate high-quality cyberspace security professionals.